Integrated solar fuel generators - Sharp, Ian D.; Atwater, Harry A. 1960-; Lewerenz, Hans-Joachim (RSC energy and environment series, 2019)
This book describes the critical areas of research and development towards viable integrated solar fuels systems, the current state of the art of these efforts and outlines future research needs.